Ethanolic extract of Anredera cordifolia (Ten.) Steenis leaves improved wound healing in guinea pigs - Isnatin Miladiyah; Bayu Rizky Prabowo (Faculty of Medicine, Universitas Trisakti, 2012)
BACKGROUNDWound healing is a normal biological process in response to skin injury. Anredera cordifolia (Ten.) Steenis is used traditionally to treat various diseases, including skin disease, hypertension, inflammation and gout. The aim of this study was to evaluate the wound healing activity of the leaves of binahong or Anredera cordifolia (Ten.) Steenis in guinea pigs. Methods Thirty guinea pigs (1.5-2 kg, 3-4 months old) were randomly divided into 5 groups. Group I was given distilled water (negative control), group II was treated with povidone iodine 10% (positive control), while groups III-V were treated with ethanolic extract of binahong leaves at concentrations of 10%, 20%, and 40%, respectively. Before treatment, a 2 cm long excision wound was made on each animal. All interventions were given by the topical route, twice daily for 15 days. At the end of 15th day, the wound lengths in each group were measured and compared to baseline wound lengths. Data were analyzed with one-way Anova to compare wound healing activity between groups. ResultsThis study showed that groups treated with ethanolic extract of binahong leaves at concentrations of 20% and 40% experienced better wound healing activity than negative and positive controls. There were significant differences (p=0.000) between treatments and negative and positive controls. ConclusionsThis research has succesfully show significance of the Binahong leaf extract has a potential for wound healing in guinea pig.